BACKSTROKE TEACHING METHODS IN HEALTHY CHILDREN WITH RESIDUAL PRIMITIVE REFLEXES - Bogdanoviča, Irina; Lāriņš, Viesturs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
There are studies suggesting that primitive reflexes can remain active in healthy children. Formal backstroke teaching is a part of many aquatic curriculum program.  Even though the links with a problem during swimming learning with retained primitive reflexes were mentioned, there are no studies about effect of different backstroke teaching methods in healthy children with residual primitive reflexes. Aim of the study is to define the effect of teaching methods for backstroke in healthy children with residual primitive reflexes. Subjects:  6-7 years old healthy children with residual primitive reflexes. Methods: A part practice backstroke teaching method for the first group (12 children) has been focused on teaching of separate components (leg kicks, arm pulls, and breathing) before fitting them together, while another 12 participants in second group learnt backstroke separate components of arm-to-leg integration before combining them together inside of cycle. After 12 weeks of practice backstroke proficiency and heart rate during maximal continuous backstroke swimming were analyzed. The obtained results show significant differences between the two groups. The results of the second group are linked with better backstroke proficiency, significantly longer swimming distance and lower heart rate during swimming.